2022
DOI: 10.1126/sciadv.abm9390
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an integrase-independent pathway of retrotransposition

Abstract: Retroviruses and long terminal repeat retrotransposons rely on integrase (IN) to insert their complementary DNA (cDNA) into the genome of host cells. Nevertheless, in the absence of IN, retroelements can retain notable levels of insertion activity. We have characterized the IN-independent pathway of Tf1 and found that insertion sites had homology to the primers of reverse transcription, which form single-stranded DNAs at the termini of the cDNA. In the absence of IN activity, a similar bias was observed with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Interestingly, a recent study has demonstrated the capability of the fission yeast Tf1 LTR retrotransposon to transpose through an integrase-independent pathway. In this system, Tf1 transposition occurs by homologous recombination mediated by the single-strand annealing protein Rad52 and not by canonical homologous recombination that would require Rad51, resulting predominantly in insertions within existing copies of related elements [58]. Rad52 homologs were identified in gymnosperms, monocots, and dicots [59] and could promote the integration of ECVs by a similar homologous recombination mechanism.…”
Section: Mechanisms Of Integrationmentioning
confidence: 99%
“…Interestingly, a recent study has demonstrated the capability of the fission yeast Tf1 LTR retrotransposon to transpose through an integrase-independent pathway. In this system, Tf1 transposition occurs by homologous recombination mediated by the single-strand annealing protein Rad52 and not by canonical homologous recombination that would require Rad51, resulting predominantly in insertions within existing copies of related elements [58]. Rad52 homologs were identified in gymnosperms, monocots, and dicots [59] and could promote the integration of ECVs by a similar homologous recombination mechanism.…”
Section: Mechanisms Of Integrationmentioning
confidence: 99%
“…In addition to the above mentioned roles, Rad52 regulates the extent of DNA resection during HR by regulating the Rqh1 helicase in fission yeast 46 . Furthermore, Rad52 functions in other processes such as regulating retrotransposition 47 , CRISPR-Cas9 genome editing 48 , and IgD class-switch recombination 49 . Given the emerging multifaceted functions of Rad52, knowledge of it functions and mechanism of action is critical.…”
Section: Introductionmentioning
confidence: 99%